2016
DOI: 10.1002/bit.26195
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive reconstruction and in silico analysis of Aspergillus niger genome‐scale metabolic network model that accounts for 1210 ORFs

Abstract: Aspergillus niger is one of the most important cell factories for industrial enzymes and organic acids production. A comprehensive genome-scale metabolic network model (GSMM) with high quality is crucial for efficient strain improvement and process optimization. The lack of accurate reaction equations and gene-protein-reaction associations (GPRs) in the current best model of A. niger named GSMM iMA871, however, limits its application scope. To overcome these limitations, we updated the A. niger GSMM by combini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…1. Firstly, according to the genome-scale metabolic model iHL1210 [24] and the transcriptomic data obtained in our previous study [7], metabolic enzymes for the biosynthetic pathways of the limited amino acids were identified and the genes involved were overexpressed in A. niger CBS 513.88, generating the mutants (Table 1). Secondly, shake flask fermentation was carried out to evaluate the glucoamylase production performance of the mutants.…”
Section: Open Accessmentioning
confidence: 99%
“…1. Firstly, according to the genome-scale metabolic model iHL1210 [24] and the transcriptomic data obtained in our previous study [7], metabolic enzymes for the biosynthetic pathways of the limited amino acids were identified and the genes involved were overexpressed in A. niger CBS 513.88, generating the mutants (Table 1). Secondly, shake flask fermentation was carried out to evaluate the glucoamylase production performance of the mutants.…”
Section: Open Accessmentioning
confidence: 99%
“…Metabolic flux analysis is the most authoritative method for measuring in vivo fluxes [47]. In this study, we used our previously updated A. niger GSMM iHL1210 [31] to predict in silico the flux distribution of the central carbon metabolic network during steady-state conditions of three strains overexpressing gndA, gsdA, and maeA, respectively. These simulation results indicated that the relative flux of the EMP and TCA cycle decreased after redirecting a higher flux through the PPP when gndA or gsdA were overexpressed, a situation which was reverse predicted when maeA was overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…These two strains have both been subject to genome studies and their genomes have been sequenced and annotated [3,4]. This paved the way for genome-scale metabolic modelling of A. niger, and to date there are three published genome-scale metabolic models (GSMM) of A. niger; iMA871 [5], iHL1210 [6], and more recently iJB1325 [7]. Genome-scale metabolic modelling opens up the possibility to couple genomic and metabolomic information with computational techniques aimed at guiding metabolic engineering strategies.…”
Section: Introductionmentioning
confidence: 99%